2017
DOI: 10.1055/s-0043-104526
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and luminal endoscopic cooperative surgery can be a standard treatment for submucosal tumors of the stomach: a retrospective multicenter study

Abstract: We have developed a combined laparoscopic and luminal endoscopic surgery technique for resection of gastric submucosal tumors (SMTs) that can be performed without excessive resection of the stomach. In a multicenter retrospective study we aimed to evaluate the feasibility and safety of laparoscopic and endoscopic cooperative surgery (LECS) for gastric SMT resection. Between October 2007 and December 2011, 126 patients with gastric SMTs underwent LECS at 8 institutions. Patient demographics, tumor histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 21 publications
(14 reference statements)
2
33
1
2
Order By: Relevance
“…The hybrid approach includes LECS, non‐exposed endoscopic wall‐inversion surgery ( NEWS ), and closed LECS . These procedures have been of increasing interest in this field in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid approach includes LECS, non‐exposed endoscopic wall‐inversion surgery ( NEWS ), and closed LECS . These procedures have been of increasing interest in this field in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports on LECS, surgical safety and therapeutic effect on the tumor still require further evaluation. The existing studies have indicated that LECS operation is a very suitable surgical method for the resection of small mesenchymal tumors [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although first reports of CELS resection in laparoscopically difficult regions like the duodenum exist, we think that these indications should be reserved to experts only [46]. CELS is predominantly and easier applicable in gastric and colonic lesions [47][48][49].…”
Section: Clinical Applicationsmentioning
confidence: 99%